Biotransformation Studies of Cresol Red by Absidia Spinosa M15 - Risky Ayu, Kristanti; Meor Mohd Fikri, Ahmad Zubir; Tony, Hadibarata (Elsevier Ltd, 2016)
Cresol Red, a commercial dye that used widely to color nylon, wool, cotton, and polyacrylonitrilemodified nylon in the massive textile manufacture is toxic recalcitrant. Absidia spinosa M15, a novel fungal strain isolated from a tropical rain forest, was found to decolorize Cresol Red 65% within 30 d under agitation condition. UVeVis spectroscopy, TLC analysis and mass spectra of samples after decolorization process in culture medium confirmed final decolorization of Cresol Red. Two metabolites were identified in the treated medium: benzeneacetic acid (tR 9.6 min and m/z 136) and benzoic acid (tR 5.7 min and m/z 122). Laccase showed the significant activity (133.8 U/L) in biomass obtained at the end of experiment demonstrates role of the enzyme in the decolorization process.